2021
DOI: 10.25311/keskom.vol7.iss2.930
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Feeding or Infants Aged 0-6 Months and The Related Factors

Abstract: Complementary food for breast milk is food or drink containing nutrition given to infants or children aged 6-24 months to meet their nutritional needs. Giving complementary foods to breast milk too early in infants can cause indigestion, diarrhea, food allergies, disturbances in appetite regulation and changes in appetite. This research was conducted in June 2019 in the Sungai Manau Health Center Work Area, Merangin Regency. This study is a descriptive study with a cross sectional design, with a sample of 96 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
1
0
2
Order By: Relevance
“…Status imunisasi anak dipengaruhi oleh usia ibu. Menurut penelitian yang dilakukan oleh Jarsiyah et al (2023), ditemukan bahwa risiko ketidaklengkapan imunisasi dasar pada anak lebih tinggi jika ibu berusia lebih dari 30 tahun dibandingkan dengan ibu yang berusia di bawah 30 tahun. Hal ini disebabkan oleh kurangnya kesadaran tentang pentingnya imunisasi pada bayi oleh ibu yang lebih tua (Jarsiyah et al, 2023).…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…Status imunisasi anak dipengaruhi oleh usia ibu. Menurut penelitian yang dilakukan oleh Jarsiyah et al (2023), ditemukan bahwa risiko ketidaklengkapan imunisasi dasar pada anak lebih tinggi jika ibu berusia lebih dari 30 tahun dibandingkan dengan ibu yang berusia di bawah 30 tahun. Hal ini disebabkan oleh kurangnya kesadaran tentang pentingnya imunisasi pada bayi oleh ibu yang lebih tua (Jarsiyah et al, 2023).…”
Section: Pembahasanunclassified
“…Menurut penelitian yang dilakukan oleh Jarsiyah et al (2023), ditemukan bahwa risiko ketidaklengkapan imunisasi dasar pada anak lebih tinggi jika ibu berusia lebih dari 30 tahun dibandingkan dengan ibu yang berusia di bawah 30 tahun. Hal ini disebabkan oleh kurangnya kesadaran tentang pentingnya imunisasi pada bayi oleh ibu yang lebih tua (Jarsiyah et al, 2023). Selain itu, ibu yang memiliki tingkat pendidikan tinggi lebih cenderung menghadapi sedikit kesulitan dalam menerima informasi, termasuk informasi tentang imunisasi yang diberikan oleh petugas kesehatan.…”
Section: Pembahasanunclassified
“…Mothers who know about MP ASI will be given MP ASI at the age of 35 months, while mothers who get good information about MP ASI will be given after the baby is more than 6 months old. (Artikasari et al 2021) (Heryanto 2017 The results of the initial survey from UPT. Hamparan Perak Health Center found that the number of babies in the work area of the Hamparan Perak Health Center from February-August 2021 was 1104 babies aged 0-6 months from 13 villages, namely: Hamparan Perak Village, Sei Baharu, Desa Lama, Alu Purau, Selemak, Klambir , Klambir Lima Kampung, Klambir Lima Kebun, Klumpang Kampung, Klumpang Kebun, Palu Purau, Payabakung, and Sialang Muda.…”
Section: Introductionmentioning
confidence: 99%